Abnormal nociception and opiate sensitivity of STOP null mice exhibiting elevated levels of the endogenous alkaloid morphine - Aunis Dominique; Van Dorsselaer Alain; Bianchi Enrica; Delalande François; Stuber Denise; Deloulme Jean-Christophe; Schweitzer Annie; Kemmel Véronique; Laux Alexis; Muller Arnaud H; Charlet Alexandre; Andrieux Annie; et al. (SAGE Publishing, 2010)
Abstract Background- Mice deficient for the stable tubule only peptide (STOP) display altered dopaminergic neurotransmission associated with severe behavioural defects including disorganized locomotor activity. Endogenous morphine, which is present in nervous tissues and synthesized from dopamine, may contribute to these behavioral alterations since it is thought to play a role in normal and pathological neurotransmission. Results- In this study, we showed that STOP null brain structures, including cortex, hippocampus, cerebellum and spinal cord, contain high endogenous morphine amounts. The presence of elevated levels of morphine was associated with the presence of a higher density of mu opioid receptor with a higher affinity for morphine in STOP null brains. Interestingly, STOP null mice exhibited significantly lower nociceptive thresholds to thermal and mechanical stimulations. They also had abnormal behavioural responses to the administration of exogenous morphine and naloxone. Low dose of morphine (1 mg/kg, i.p.) produced a significant mechanical antinociception in STOP null mice whereas it has no effect on wild-type mice. High concentration of naloxone (1 mg/kg) was pronociceptive for both mice strain, a lower concentration (0.1 mg/kg) was found to increase the mean mechanical nociceptive threshold only in the case of STOP null mice. Conclusions- Together, our data show that STOP null mice displayed elevated levels of endogenous morphine, as well as an increase of morphine receptor affinity and density in brain. This was correlated with hypernociception and impaired pharmacological sensitivity to mu opioid receptor ligands.